Vibration reduction control for redundant flexible robot manipulators. Issue 2 (2020) - Rahmouni, Mohamed Amine; Bearee, Richard; Grossard, Mathieu; Lucet, Eric
Abstract: In this paper, both vibration reduction and task accuracy improvement for flexible redundant manipulators, using the resolution of redundancy, is addressed. The exciting force of flexural motion, which is induced by the motion of the manipulator, causes undesired deflection at the end-effector. The null space inherent in redundancy feature is exploited to damp out the vibration while maintaining the end-effector posture. In order to exploit all the degrees of freedom in the null space, a feedback control design based on torque optimization has been introduced using analytical method for the redundancy resolution. The simulation analysis is presented to test the effectiveness of the proposed approach.